1972
DOI: 10.1515/cclm.1972.10.9.410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Alcohol Abuse on the Structural Lipids in the Human Brain

Abstract: Eight human brains with clinical signs of "hepatocerebral degeneration" (6 alcoholic and 2 post hepatitic in aetiology) were examined in 4 different regions for their content of cerebroside, sphingomyelin, phosphatidyl choline, phosphatidyl ethanolamine, and cholesterol. Compared with normal brains the lipid content was reduced in all these regions. The grey matter showed mainly a reduction of cerebroside, whereas significant loss of cerebroside, phosphatidyl choline, phosphatidyl ethanolamine, and cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Pathological studies have confirmed a loss of brain volume relative to cranial capacity, with a reduction in white matter volume rather than cortical grey matter (Harper et al 1985). These volume changes in white matter may be associated with changes in sodium and potassium concentrations (Shaw et al 1969) and lipid content (Lesch et al 1979), and alterations in hydration may explain the potential reversibility of" CT scan changes. Tj values in general reflect the water content of tissue (Mathur de Vre, 1984) but the increase in T t values in newly detoxified alcoholics does not appear to be a potentially reversible phenomenon (Chick et al 1987;.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological studies have confirmed a loss of brain volume relative to cranial capacity, with a reduction in white matter volume rather than cortical grey matter (Harper et al 1985). These volume changes in white matter may be associated with changes in sodium and potassium concentrations (Shaw et al 1969) and lipid content (Lesch et al 1979), and alterations in hydration may explain the potential reversibility of" CT scan changes. Tj values in general reflect the water content of tissue (Mathur de Vre, 1984) but the increase in T t values in newly detoxified alcoholics does not appear to be a potentially reversible phenomenon (Chick et al 1987;.…”
Section: Discussionmentioning
confidence: 99%
“…First, Harper et al (1987) reported that the number of cortical neurons in the superior frontal cortex was significantly reduced in chronic alcoholics with or without WE compared with controls, whereas neuronal counts were equivalent in the motor cortex. Secondly, frontal white matter pathology has been demonstrated in alcoholics on the basis of biochemical findings (Lesch et al 1979) and changes in CT absorption values (Gurling et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…However, Lynch (1960) has described white matter changes in "ordinary" alcoholics. Further, in brains from subjects with alcoholic liver disease, Lesch et al (1972) found a significant loss of structural lipids in myelin rich areas. Alling & Bostrom (1980) also described loss of myelinated fibres and decreased concentration of cerebrosides, cholesterol and phospholipids in the mamillary bodies of brains from alcoholics.…”
Section: Discussionmentioning
confidence: 92%